Mandibular Fractures: Diagnosis and Management - Panesar, Kanvar; Susarla, Srinivas M. (Seminars in Plastic Surgery, 2021)
Accurate evaluation, diagnosis, and management of mandibular fractures is essential to effectively restore an individual's facial esthetics and function. Understanding of surgical anatomy, fracture fixation principles, and the nuances of specific fractures with respect to various patient populations can aid in adequately avoiding complications such as malocclusion, non-union, paresthesia, and revision procedures. This article reviews comprehensive mandibular fracture assessment, mandibular surgical anatomy, fracture fixation principles, management considerations, and commonly encountered complications. In addition, this article reviews emerging literature examining 3-dimensional printing and intraoperative imaging.
Keywords: mandible; mandibular fracture; maxillofacial injury; craniomaxillofacial trauma; facial trauma